Investigation of cortical and sub-cortical processing of pressure pain transduction in healthy controls and chronic lumbar radicular pain pre and post oxycodone treatment-An event related fMRI study. - KASABA SRINIVASAIAH, HARI (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
Background: - Few scientific developments have been more striking than the ability to measure the activity of the functioning human brain. Experimental acute pain stimulus in healthy controls can predict with more than 90% accuracy whether a thermal stimulus is just warm or painfully hot. Unlike acute pain, chronic pain patients show a shift in brain pain signatures. Activation of the insula is commonly associated with acute pain while in chronic pain brain activations are observed in the medial prefrontal cortex, which is associated with higher cognitive abilities such as memory and decision-making, and the amygdala, which plays a central role in emotional processing. Methods: -Twenty-four right-handed healthy controls and Seventeen right-handed patients with a diagnosis of chronic lumbar radicular pain as defined by history, physical exam and MRI scan, were recruited. A custom-built electronic pressure algometer was used to deliver pressure stimuli of different magnitudes (1, 2 and 3 bar). Each participant was scanned while being stimulated by the electronic algometer running one of the four experimental sequences. The experimental design was optimized for efficiency by a fixed blunt pressure stimulus of 5 seconds and varying inter-stimulus duration between 4 and 14 seconds. Chronic pain subjects included in the study received 10 milligrams oral Oxycodone twice daily after first scan for seven days (7 days) prior to the second scan. Results: -The present study demonstrated greater activations in bilateral anterior insula cortex, thalamus, p ACC, a MCC and p MCC and d PCC, cerebellum, superior, middle and inferior frontal gyrus, middle temporal gyrus, SMG, S I, SII and motor cortex in healthy controls. We had hypothesized that the chronic pain patients would demonstrate greater brain activation to the pressure pain stimuli than the controls. However, contrary to our prediction, the present study found less cortical and sub-cortical activation in brain areas in patients with chronic pain compared to healthy controls. This study demonstrated activations in superior, middle and inferior frontal gyrus, anterior and middle cingulate, lentiform nucleus, insula, cerebellum, superior temporal gyrus, para-hippocampal gyrus, primary somatosensory area, inferior parietal lobe, thalamus and amygdala. We had hypothesized that the chronic pain patients after oral oxycodone treatment would demonstrate lesser brain activation to the pressure pain stimuli than pre-oxycodone treatment However, contrary to our prediction, the present study demonstrated more cortical and sub-cortical activation in brain areas including cerebellar activation in patients with chronic pain after treatment with oxycodone. Conclusion: - Healthy volunteers demonstrated more brain activation compared to both pre and post oxycodone treated chronic pain patients. The Oxycodone therapy resulted in more brain activation in patients with chronic pain and this may be explained by gray matter regeneration. This is consistent with multiple researchers reporting partial reversibility in neuronal degeneration with effective treatment of chronic pain.
APPROVED